Considering The use of Artificial Intelligence in The Board of Directors: A Corporate Law Review - Yolanda Simbolon (Universitas Muhammadiyah Surakarta, 2025)
Director is one of the crucial organs in a Limited Liability Company. The Director has great trust in managing the company. Some companies have placed Artificial Intelligence on the board of directors. This is because Artificial Intelligence can make decisions efficiently and independently. This raises legal issues regarding whether Artificial Intelligence can become a board of directors or is there another alternative and how about the responsibility. The aim of this article is to contribute to the development of company law in the future which is related to Artificial Intelligence. The method of this research is normative juridical. This research also uses a conceptual approach. The data used to analyze is secondary data. This research has novelty compared to other similar studies because the approach used is corporate law, especially in relation to the principle of fiduciary duty and business judgment rules. The results show that Artificial Intelligence currently cannot be placed as a member of the board of directors. As an alternative, Artificial Intelligence can be used as a business advisor on the board of directors.